A Randomized Trial of Real‐Time Geriatric Assessment Reporting in Nonelectively Hospitalized Older Adults with Cancer. (27th January 2020) - Jolly, Trevor A.; Deal, Allison M.; Mariano, Caroline; Markowski, Nicole; Kirk, Sharanda; Perlmutt, Max S.; Jones, Franklin; Choi, Suel Ki; Nyrop, Kirsten A.; Busby‐Whitehead, Jan; Muss, Hyman
Abstract: Background: Hospitalized older adults have significant geriatric deficits that may lead to poor outcomes. We conducted a randomized trial to investigate the effectiveness of providing clinicians with a real‐time geriatric assessment (GA) report in nonelectively hospitalized older patients with cancer. Subjects, Materials, and Methods: We developed a web‐based software platform for administering a modified GA (Cancer 2005;104:1998–2005) to older (>70 years) nonelectively hospitalized patients with pathologically confirmed malignancy. Patients were randomized to have their GA report provided to their treating clinicians (Intervention arm) or not provided (Control arm). Results: Our study included 135 patients, median age 76 years, 52% female, 75% white, 21% black, 79% greater than high school education, 59% married, and 17% living alone. All patients had at least one GA‐identified deficit, including physical function deficits (90%), cognitive impairment (22%), >5 comorbidities (28%), polypharmacy (>9 medications; 38%), weight loss ≥10% in the past 6 months (40%), anxiety (32%), or depression (30%). There was no difference between the Intervention (6%) and Control arms (9%) in the proportion of patients who were referred by their clinical team for an intervention to address a deficit ( p = .53). Conclusion: Many older nonelectively hospitalized patients with cancer have geriatric deficits that are amenable to evidence‐based interventions. Real‐time GA reports provided to the care team prior to discharge did not influence provider referral for such interventions. There is a need for systems‐level interventions to address deficits in this vulnerable patient population. Implications for Practice: Geriatric deficits are common in hospitalized older adults with cancer and lead to poor outcomes. Addressing modifiable deficits represents an appealing way to improve outcomes. Widespread geriatrician consultation is impractical owing to resource and personnel constraints. This work tested whether prompt delivery of a mostly self‐administered, web‐based geriatric assessment report to clinicians improved referral rates for evidence‐informed interventions. It confirmed frequent geriatric deficits and high readmission rates in this population but found that real‐time geriatric assessment reporting did not influence provider referral for evidence‐informed interventions on geriatric assessment identified deficits. These findings highlight the need for systems‐level intervention to improve outcomes in this vulnerable patient population. Abstract : To improve cancer care outcomes in older adults, timely identification of age‐related functional impairments is needed. This article describes a randomized trial that was conducted to test a real‐time geriatric assessment aimed at identification of and interventions for age‐related deficits.